Market Access Limitations of the Philippines in the EU Market - Christine Marie Liao; Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2007)
Nontariff measures are everywhere vilified for preventing exports, especially of agriculture, from developing countries. Philippine exporters seem to be taking things in stride, however. The paper estimates the cost of certification regularly borne by a typical Philippine food exporter to be less than three percent of sales, a relatively inconsequential ratio. However, increased cost from NTMs can adversely affect the small-scale companies that lack resources to adapt their production processes to foreign standards. The paper also traces the Philippine export products affected by nontariff measures imposed by the European Union. In all, NTMs of the EU affect a total of US34 million of Philippine agriculture and fish exports to these markets, representing almost seven percent of agriculture exports to the twenty-five countries.
Keywords: 330; market access; nontariff measures; Philippine agricultural exports; European Union; sanitary and phytosanitary (SPS) measures; Nichttarifäre Handelshemmnisse; Agraraußenhandel; Philippinen; Markteintritt; Standardisierung; EU-Staaten